A Pro-Inflammatory Diet Is Associated With an Increased Odds of Depression Symptoms Among Iranian Female Adolescents: A Cross-Sectional Study - Shivappa, Nitin; Hebert, James R.; Neshatbini Tehrani, Asal; Bayzai, Bita; Naja, Farah; Rashidkhani, Bahram (Frontiers in Psychiatry, 2018)
Background: The relation between dietary inflammation and risk of depression has not been widely explored. We examined the association between the inflammatory effect of the diet and the odds of depression among Iranian female adolescents. Methods: Using a stratified cluster sampling technique, 300 female adolescents aged 15-18 years were recruited from schools in Tehran between years 2014-2015. Depression was assessed using the Depression, Anxiety and Stress Scale (DASS)- a 21-point scale. The dietary inflammatory index (DII®) was used to evaluate the inflammatory potential of the diet. Dietary intake was assessed using a validated food frequency questionnaire. In addition to descriptive statistics, multivariable linear and logistic regression were used to calculate confounder-adjusted beta estimates and odds ratios. Results: In total, 88 females (30%) had at least a moderate level of depressive symptoms (DASS>6). Females with the most pro-inflammatory diet had higher DASS depression score (β=1.67; 95% CI=0.03, 3.31) and were at 3.96 (95% CI=1.12, 13.97) times higher odds of having at least moderate depressive symptoms, compared to females with the least anti-inflammatory diets. Conclusion: These data suggest that Iranian adolescent females eating a pro-inflammatory diet, as indicated by higher DII scores, had greater odds of having at least moderate depressive symptoms.